2010
DOI: 10.1007/s10705-010-9413-1
|View full text |Cite
|
Sign up to set email alerts
|

Field balances and recycling rates of micronutrients with various fertilization treatments in Northeast China

Abstract: Due to their effects on human health, recent research in China has focused on the status of micronutrients in agro-ecosystems. In this study, we analyzed the concentrations of available micronutrients in cropping systems, their recycling rates in the feeding-composting cycle, and their field balances. Our results showed there were significant differences in the concentration of available micronutrients among treatments, with micronutrients found highest in the NPK ? M (recycled pig manure) treatment. The recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…Grain Zn concentration was influenced neither by PD nor by N rate. A similar lack of N rate effect on grain Zn was documented by Bruns and Ebelhar (2006), Riedell et al (2009), and Yu et al (2011). Minor N rate effects on grain Ca but more significant N rate effects on grain Mg concentrations were reported by Feil et al (2005).…”
Section: Resultssupporting
confidence: 71%
“…Grain Zn concentration was influenced neither by PD nor by N rate. A similar lack of N rate effect on grain Zn was documented by Bruns and Ebelhar (2006), Riedell et al (2009), and Yu et al (2011). Minor N rate effects on grain Ca but more significant N rate effects on grain Mg concentrations were reported by Feil et al (2005).…”
Section: Resultssupporting
confidence: 71%
“…As well as being similar among treatments, the maize grain concentrations of Fe, Mn, Cu, and Zn were similar to those found by Berenguer et al (2008), Li et al (2007), Yu et al (2011) and surveys of maize grown in the Hebei province of China (Jia et al, 2009). However, the Cu concentrations were clearly too low to meet the physiological requirements of ruminant animals (9-11 mg kg −1 ; McDowell, 2003), which is a source of concern since maize grain is commonly used for feeding animals in the study region.…”
Section: Micronutrient Concentrations In Grain and Strawsupporting
confidence: 82%
“…Application of chemical NPK fertilizer alone resulted in negative balances of all four micronutrients. Yu et al (2011) found balances of the four elements to be positive under all treatments they considered in a single cropping system in northeast China. However, this was mainly due to high inputs through deposition (3.720, 1.112, 0.142, and 0.544 kg ha −1 a −1 of Fe, Mn, Cu, and Zn, respectively), while in the system we examined deposition was negligible (Table 4).…”
Section: Micronutrient Uptake and Balancementioning
confidence: 90%
“…Some characteristics of the tested soil were as follows: organic matter 20.9 g kg −1 , total N 1.13 g kg −1 , total P 0.44 g kg −1 , total K 16.4 g kg −1 , available P 10.6 mg kg −1 , available K 88.0 mg kg −1 , pH 6.5 (Yu et al 2011). Twokilogram air-dried soil was packed at approximately 1.25 g cm −3 bulk density, and the depth of the soil was about 11 cm in each jar.…”
Section: Experimental Designmentioning
confidence: 99%